ISLAM YANG RAHMAT DALAM MEMBANGUN UMAT STUDI TERHADAP DAKWAH PAIF KABUPATEN SLEMAN - Subejo, H.M. Kholili, Syamsul Hadi, dan (Jurnal Kawistara, 2014)
Islamic that mercy has been encouraging for his people, therefore Islamic concept that was delivered by Islamicpreachers has given benefit and welfare of the inner and outer life. In fact, poor Muslim population reaches23 %, while most of them have not been routinely practicing the tought of Islam. This paper aims to analyzethe competence factor of preachers (PAIF) effect on the activity of preaching; and analyze the preachingcomponents a PAIF affects to preaching effects. This research was conducted in Sleman Yogyakarta by usinga mixed method of quantitative analysis that is supported by SEM analysis techniques. The research resultsshowed that: a PAIF required to has competence in understanding the socio-cultural and communicate well sothat he can design the preaching messages that fit to the needs of targeted community. Encouraging preachingactivities can be organized through: setting the theme of preaching messages that support the needs of followers;presented by giving motivation; balancing the use of preaching methods and the preaching extension methods,as well as utilizing other forms of communication appropriately and optimally.